(3cJGH JYLjR GdeSJYLRs - (3YeQ Hf NVQ Hf YeQ GdCUagGfjs ((3eMeO Hf eMeO GdbhUhfi s)
(3ChdgG (B:s
(3GdMeO ddg YdG Ydi eG YOGg ef GdehLhOGJ CeG HYO aEfi fXQJ ai bhGYO GdadGSaI hYbGFOge QCjJ GdNWC ajgG CcKQ ef GdUhGH s
(3BNQgG (B:s
(3aGdCTjGA GdeJbOeI Ydi TF dGjLH Cf Jchf eYkG hgPG BNQ eG JjSQ PcQg ef JYLjR GdeSJYLR hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs